REKONSTRUKSI PEMIDANAAN DALAM HUKUM PIDANA ISLAM (PERSPEKTIF FILSAFAT HUKUM) - Ahmad Syafiq (Jurnal Pembaharuan Hukum, 2014)
Islamic Criminal Law is a living law in Indonesia, and that the Islamic Criminal Law be enacted or coloring in the criminal law in Indonesia, hence the need for a reconstruction against Islamic Criminal Law, especially in theories of punishment. Reconstruction of punishment in the Islamic Criminal Law in the perspective of legal philosophy can be done by doing the desecration (reinterpretation of the textual sources of law) Islamic Criminal Law and bring it in line with the flow of human history itself, rather than release it from the dimensions of space and time history of human civilization, to realize the goals of Islamic law is philosophically contained in maqasid al shariah ie benefit or blessing for the universe (rahmatan lil 'alamin).